Peran Kepala Sekolah dalam Penyelenggaraan Bimbingan dan Konseling di Sekolah - Zulhelmi Narti; Neviyarni S; Firman Firman (Universitas PGRI SUMATERA BARAT, 2023)
The success of implementing guidance and counseling in schools is highly dependent on the collaboration carried out by the guidance and counseling teacher or counselor and the assistance and support of all parties in the school, such as subject teachers, homeroom teachers, education staff, vice principals, and heads of school administrators. and school manager. As a leader and manager, school principals are required to be able to carry out their roles, responsibilities and functions, especially in carrying out guidance and counseling in schools properly so that the implementation of guidance and counseling can be carried out optimally. In other words, the good or bad quality of all service programs in schools and the counselor's image depend on how the leader or manager plays his role appropriately. The method used in this research is the library research method (literary research). This study aims to examine the role of school principals in the implementation of guidance and counseling in schools. Keywords: Guidance and counseling, headmaster, counselor, the role of school principals